Identification of a novel class of autotaxin inhibitors through cross-screening1. Issue 6 (10th June 2015) - Castagna, Diana; Duffy, Emma L.; Semaan, Dima; Young, Louise C.; Pritchard, John M.; Macdonald, Simon J. F.; Budd, David C.; Jamieson, Craig; Watson, Allan J. B.
<x xml:space="preserve">Abstract</x> Starting from the known LPA1 antagonist 4, three novel series of autotaxin inhibitors exemplified by 7, 8 and 9 were identified using a combination of scaffold hopping and ligand-based design.